Comparison of 3D games’ efficiency with use of CRYENGINE and Unity game engines - Żukowski, Hubert (Journal of Computer Sciences Institute, 2019)
This article presents the results of the performance studies of applications created with use of CryEngine and Unity game engines. Presented research was mainly focused on comparison of two applications created on selected engines. Several parameters were selected for the research: frame rate, CPU usage, RAM usage and generation time of 3D objects. Created applications were built with the use of the same graphic resources and similar source code. The hypotheses set in the article – Unity game engine is more efficient than CryEngine – have been verified and partially confirmed: engines are more efficient in different environments.